2015
DOI: 10.1128/jvi.01466-15
|View full text |Cite
|
Sign up to set email alerts
|

Encapsidation of Host RNAs by Cucumber Necrosis Virus Coat Protein during both Agroinfiltration and Infection

Abstract: Next

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 63 publications
(99 reference statements)
8
20
1
Order By: Relevance
“…In summary, our work reveals that genome-encoded circRNAs carrying a self-cleaving ribozyme like the HHR are frequent molecules in plant transcriptomes, and constitute a feasible source for the origin of some virus satellites and viroids. In this regard, host RNAs derived from Ty3-gypsy retroelements are known to be efficiently encapsidated by the coat protein of a plant virus [ 56 ], and also Ty1-copia retrotransposons have already been proposed as the origin of non-HHR viroids of the family Pospiviroidae [ 57 ]. Finally, a plethora of splicing-derived circRNAs with diverse biological functions have been recently reported in eukaryotes [ 58 64 ] and, consequently, future research will be focused on deciphering the possible roles and biotechnological applications of genome-encoded circRNAs with HHRs.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our work reveals that genome-encoded circRNAs carrying a self-cleaving ribozyme like the HHR are frequent molecules in plant transcriptomes, and constitute a feasible source for the origin of some virus satellites and viroids. In this regard, host RNAs derived from Ty3-gypsy retroelements are known to be efficiently encapsidated by the coat protein of a plant virus [ 56 ], and also Ty1-copia retrotransposons have already been proposed as the origin of non-HHR viroids of the family Pospiviroidae [ 57 ]. Finally, a plethora of splicing-derived circRNAs with diverse biological functions have been recently reported in eukaryotes [ 58 64 ] and, consequently, future research will be focused on deciphering the possible roles and biotechnological applications of genome-encoded circRNAs with HHRs.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the latter possibility, we analyzed the level of VLPs that accumulated in the above-described experiment at 6 dpai. We recently found that pCNVCPpBin(ϩ)-agroinfiltrated plants accumulate VLPs that harbor host RNA (65). The particles consist of both Tϭ3 and Tϭ1 icosahedra and intermediate-sized (IS) spherical particles of unknown icosahedral symmetry (unpublished observations).…”
Section: Resultsmentioning
confidence: 90%
“…N. benthamiana plants were agroinfiltrated with pCNVCPpBin(ϩ), which is a binary vector that expresses the CNV CP, as described previously (65). Agroinfiltration was performed in the presence of pNbHsc70-2/pBin(ϩ), which encodes N. benthamiana Hsc70-2 (see below), or pGFP/pBin(ϩ), which expresses green fluorescent protein (GFP) as a control.…”
Section: Methodsmentioning
confidence: 99%
“…In plants, Ghoshal et al. [28] showed that cucumber necrosis virus can encapsidate TEs from their host (Nicotiana benthamiana). These three possible routes of HTs are schematized in Fig.…”
Section: Mechanisms Of Horizontal Transfersmentioning
confidence: 99%